Cerebral Microcirculation during Experimental Normovolaemic Anemia - Bellapart, Judith; Cuthbertson, Kylie; Dunster, Kimble; Diab, Sara; Platts, David G.; Raffel, O. Christopher; Gabrielian, Levon; Barnett, Adrian; Paratz, Jenifer; Boots, Rob; Fraser, John F. (Frontiers in Neurology, 2016)
Anaemia is accepted amongst critically ill patients as an alternative to elective blood transfusion. This practice has been extrapolated to head injury patients with only one study comparing the effects of mild anaemia on neurological outcome. There are no studies quantifying microcirculation during anaemia. Experimental studies suggest that anaemia leads to cerebral hypoxia and increased rates of infarction, but the lack of clinical equipoise when testing the cerebral effects of transfusion amongst critically injured patients, supports the need of experimental studies. The aim of this study was to quantify cerebral microcirculation and the potential presence of axonal damage in an experimental model exposed to normovolaemic anaemia, with the intention of describing possible limitations within management practices in critically ill patients. Under non-recovered anaesthesia, six Merino sheep were instrumented using an intracardiac transeptal catheter to inject coded microspheres into the left atrium to ensure systemic and non-chaotic distribution. Cytometric analyses quantified cerebral microcirculation at specific regions of the brain. Amyloid precursor protein staining was used as an indicator of axonal damage. Animals were exposed to normovolaemic anaemia by blood extractions from the indwelling arterial catheter with simultaneous fluid replacement through a venous central catheter. Simultaneous data recording from cerebral tissue oxygenation, intracranial pressure and cardiac output was monitored. A regression model was used to examine the effects of anaemia on microcirculation with a mixed model to control for repeated measures. Homogeneous and normal cerebral microcirculation with no evidence of axonal damage was present in all cerebral regions, with no temporal variability, concluding that acute normovolaemic anaemia does not result in short term effects on cerebral microcirculation in the ovine brain.